2022
DOI: 10.3390/ijms231911977
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Improves the Digestive Ability and the Intestinal Health of Siberian Sturgeon

Abstract: The lack of detailed information on nutritional requirement results in limited feeding in Siberian sturgeon. In this study, resveratrol, a versatile natural extract, was supplemented in the daily diet, and the digestive ability and microbiome were evaluated in the duodena and valvular intestines of Siberian sturgeon. The results showed that resveratrol increased the activity of pepsin, α-amylase, and lipase, which was positively associated with an increase in the digestive ability, but it did not influence the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…OB ≥30% is considered 'drug-like'. Although the OB of Res is only 19.07%, there is growing evidence of the therapeutic potential of Res for intestinal health (58). But the relatively low OB and rapid metabolism of Res may limit its use in humans (59).…”
Section: Discussionmentioning
confidence: 99%
“…OB ≥30% is considered 'drug-like'. Although the OB of Res is only 19.07%, there is growing evidence of the therapeutic potential of Res for intestinal health (58). But the relatively low OB and rapid metabolism of Res may limit its use in humans (59).…”
Section: Discussionmentioning
confidence: 99%
“…Environmental stresses (temperature, ammonia nitrogen, toxicant, etc) negatively impact the sh's metabolic balance, and reactive oxygen species and in ammation levels, ultimately affecting the yield and quality and even leading to mortality [5][6][7][8][9][10]. To mitigate the adverse effects and risks, several studies have suggested the supplementation of dietary additives, such as plant and animal extracts, bene cial probiotics, microalgae, and other substances [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it has been utilized as an aquafeed additive to enhance the quality and economic value of aquatic products. In certain studies, resveratrol bene ts to the gut health of Siberian sturgeon by improving the structure of intestinal villi and the abundance and composition of microbial communities [14]. Additionally, it has been found to ameliorate the effects of a high-fat diet on hepatic antioxidant, in ammation, and lipid metabolism in carp (Cyprinus carpio) [22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations